The impact of flood risks on urban expension areas in cities (Case study of M’sila, Algeria) - Chouki, Ramadane Chikouche; Makhloufi, Hadjab (Technium Social Sciences Journal, 2022)
Natural disasters and their causes are so complex and difficult to classify that some types have sudden impacts while other types have slow impacts on urban expansion areas. Flood is one of the most serious natural disasters affecting the urban environment. On the physical side, flood causes destruction of buildings and cuts in the urban fabric. However on the environmental side, flood’s impacts appear inthe presence of swamps and ponds and which cause, in turn, the spread of bad odors, epidemics and diseases via running water. The latter may have a greater impact on infrastructure such as bridges, roads and the lives of residents. As for M’sila region, whenever there is heavy and sudden rain, the neighborhoods and residential communities located along El-Ksob valley, as well as the area of urban expansion, are exposed to torrential floods due to the high level of the valley water as well as El-Mwailha valley, which is located within the area of land occupancy plan(HammamDal’a Road). These floods have resulted in large losses in buildings and properties, and in some cases, victims. Therefore, this study discusses some risks caused by floods on the urban expansion areasin M’sila and tries to provide solutions to reducethe severity of this phenomenon